Concerns and Needs of Teacher Education Students in Gender-Based Research - Pecson, Ryan (Indonesian Journal of Education Teaching and Learning (IJETL), 2025)
Gender-based research is vital for advancing gender equality and social justice, making it imperative for teacher-education students to be well-equipped in this area to foster inclusive and equitable education practices. With that, the study assessed and compared the concerns of needs of teacher education students in gender-based research as the baseline for the provision of a comprehensive support system. Using the descriptive survey design of quantitative research, the data are gathered from students enrolled in the various programs under the College of Education (COEd) who have conducted gender-based research. A questionnaire was used as the data gathering tool, wherein the results were analyzed using descriptive statistics. The analysis revealed that bias and stereotyping are the most pressing concerns, followed by gender equality/inequality and discrimination. Ethical considerations were also significant. Respondents primarily sought guidance and support, training and education, and ethical guidance, underscoring the need for a comprehensive support system to address these issues effectively. This study is crucial for the teacher education program and aligns with Sustainable Development Goal (SDG) No. 5 (Gender Equality) by identifying the concerns and needs of students in gender-based research, thereby informing the development of a comprehensive support system to promote gender equality and inclusive education practices.